2018
DOI: 10.1371/journal.pone.0204838
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of STAF score in combination with D-dimer in cardioembolism

Abstract: The aim of this study was to evaluate the diagnostic value of the Score for the Targeting of Atrial Fibrillation (STAF) in combination with the serum D-dimer (DD) levels in cardioembolism(CE).This study was a retrospective case-onlystudy, consecutively including patients with acute ischemic stroke. All patients were evaluated following the STAF scoring criteria and were classified according to the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) etiology classification criteria. A total of 317 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…31 Some studies reported elevated D-dimer values were more predictive of cardiogenic stroke when combining with B-type natriuretic peptide and a clinical predictive score for occult AF in stroke patients. 8,32 Prediction of recurrent stroke D-dimer measurement may be useful for evaluating the risk of recurrent stroke in cryptogenic stroke. Previous studies showed that D-dimer levels in full cohorts including all etiologies with acute ischemic stroke were not predictive of long-term recurrent stroke.…”
Section: Cryptogenic Stroke/embolic Stroke Of Undetermined Source Etimentioning
confidence: 99%
“…31 Some studies reported elevated D-dimer values were more predictive of cardiogenic stroke when combining with B-type natriuretic peptide and a clinical predictive score for occult AF in stroke patients. 8,32 Prediction of recurrent stroke D-dimer measurement may be useful for evaluating the risk of recurrent stroke in cryptogenic stroke. Previous studies showed that D-dimer levels in full cohorts including all etiologies with acute ischemic stroke were not predictive of long-term recurrent stroke.…”
Section: Cryptogenic Stroke/embolic Stroke Of Undetermined Source Etimentioning
confidence: 99%
“…It has been confirmed [7] that STAF can be used to effectively diagnose atrial fibrillation in cerebral infarction cases and aid in tracking patients' condition progression following cerebral infarction, and a separate study demonstrated that STAF scores were notably higher in CE patients compared to NCE patients. Furthermore, STAF's diagnostic utility for CE patients surpassed that of cardiac troponin I, underscoring its value as a reliable reference for predicting CE diagnoses [17]. In this study, STAF was higher in patients from the CE group compared to those in the NCE group, demonstrating a clear association between STAF and the occurrence of CE in patients.…”
Section: F I G U R E 2 Roc Curves Of Right Heart Contrast Echocardiog...mentioning
confidence: 57%